1986
DOI: 10.1159/000124547
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by Which Picrotoxin and a High Dose of Diazepam Elevate Plasma Corticosterone Level

Abstract: Picrotoxin (1 mg/kg, i.p.) and a high dose of diazepam (10 mg/kg, i.p.) increased the concentration of plasma corticosterone in nonstressed rats. This effect of diazepam was unaffected by picrotoxin and bicuculline (GABA-A receptor blockers), atropine (a muscarinic receptor blocker), apomorphine (a dopamine receptor agonist), haloperidol (a dopamine receptor blocker) and yohimbine (an alpha-2-adrenergic receptor blocker); but was blocked by clonidine (an alpha-2-receptor agonist) and this effect of clonidine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…The blockade was achieved with a dose (0.5 mg/kg) which failed to affect plasma ACTH and corticosterone levels. Other in vivo studies show that picrotoxin (in doses of 1 mg/kg and higher) increases corticosterone secretion (Makara and Stark, 1974;Ixart et al, 1983;Peri~i6 et al, 1985;Laki6 et al, 1986). Our dose-response for picrotoxin confirmed the previous results.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The blockade was achieved with a dose (0.5 mg/kg) which failed to affect plasma ACTH and corticosterone levels. Other in vivo studies show that picrotoxin (in doses of 1 mg/kg and higher) increases corticosterone secretion (Makara and Stark, 1974;Ixart et al, 1983;Peri~i6 et al, 1985;Laki6 et al, 1986). Our dose-response for picrotoxin confirmed the previous results.…”
Section: Discussionsupporting
confidence: 90%
“…With aim to elucidate the mechanism by which the lower dose of diazepam suppresses the HPA axis activity, we tried to counteract these inhibitory effects of diazepam on plasma ACTH and corticosterone levels in female rats with the antagonists of central (flumazenil; Hunkeler etal., 1981), and peripheral (PKl1195 or 1-(2-chlorophenyl)-Nmethyl-(1-methylpropyl-3-isoquinolinecarboxamide; Le Fur etal., 1983) benzodiazepine receptors and the antagonists of GABA (bicuculline) and GABA-A receptor coupled chloride channels (picrotoxin) (Olsen, 1982). As we have already shown in details the dose response effects and the time course of diazepam on plasma corticosterone levels (Peri6i6 et al, 1984) together with the mechanism of action of higher dose of diazepam on the HPA axis (Laki6 et al, 1986), in this paper we focused our attention on the effect of a lower dose of diazepam on the HPA axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A va riety of clonidine responses has been shown to be mediated through postsynaptic «2-adrenergic receptors including re duction in cardiovascular function [27] and antagonism of elevated plasma corticosterone produced by various treat ments [16,29,53,54,62]. In support of this hypothesis that clonidine acts postsynapticaily at the level of the hypotha lamus to reduce CRF secretion, recent studies have shown ct2-adrenergic receptors to be localized on CRF-containing neurons in the paraventricular nucleus (PVN) [10].…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, this neu rotransmitter is mainly noted for its anticonvulsive and anxiolytic [21] as well as antiaggressive [6,26] behavioral effect. Currently, endocrine studies have also demon strated that BZ is involved in the hormonal secretion from both pituitary [12,15] and peripheral endocrine tissues [3], The above results have aroused interests towards the characterization of BZ receptors in rodent CNS [28,29] and hence it is not surprising that most biochemical and distribution data of the BZ receptors are basically con fined to mammalian species. In fact, recent studies have revealed a hormone-dependent regulation of BZ recep tors in the different brain areas of the rat [7,10],…”
mentioning
confidence: 99%